Dietary shifts and the need for increased sustainability approaches in the global aquaculture seafood system - Mizuta, Darien D. (Frontiers in Sustainable Food Systems, 2024)
Recent shifts in the global dietary preferences have indicated the fast-growing choice for plant-based, or meat-reduced diets. Among the motivations for such choices, which are increasingly advocated by nations and environmental institutions, is the major concern with global environmental sustainability and impacts of food production systems. Incontestably, the animal food source industry is extremely diverse, and seafood production through the aquaculture value chain remains unfamiliar to key stakeholders possibly leading to an uncomprehensive view and often biased perception of the farming industry within the environmental context. Accordingly, I discuss the importance of seafood production systems, such as the fastest seafood production that is the aquaculture sector, to increase their focus on the sustainability arena with more substantial and effective improvements for sustainable production, and most importantly, concomitantly informing end consumers. I mention examples of types of sustainability efforts that can be implemented and highlight the urgency of actively informing customers about implemented practices.